Application of CO2-storage materials as a novel plant growth regulator to promote the growth of four vegetables. (July 2018) - Zhao, Long; Liu, Chang; Yue, Xiaoqing; Ma, Liang; Wu, Yu; Yang, Tingyu; Zhang, Jianbin
Highlights: CO2 SMs promising as indirect CO2 sources to promote growth of plants. Shorter florescence and higher plant yield elicited by CO2 SMs. Strong stability of CO2 SMs at room temperature for transportation and storage. Strongest effect of CO2 SMs fertilizer observed the growth of cucumber. Abstract: In the present work, CO2 -storage materials (CO2 SMs) obtained from CO2 capture were applied as energy sources to facilely boost the growth of four vegetables including eggplant, tomato, pimiento, and cucumber. The effects of CO2 SMs on the vegetable growth were determined by irrigating plants with different CO2 SMs fertilizers for 60 d using water and NH4 HCO3 as the control groups. The results indicated that all CO2 SM fertilizers dramatically promoted the plant growth of the tested vegetables in terms of plant height, stem diameter, and root development. Further investigation revealed that CO2 in CO2 SMs functioned as an indirect energy source to improve the root development, which increased the absorption of nutrients from the soil to further promote both vegetative growth florescence and yield. Our work has provided a new strategy for CO2 utilization as an indirect energy source.